Exploration of the antidiabetic potential of the leaves of Tetracera scandens Linn., (Mempelas Kesar) in alloxan induced diabetic wister rats - Ahmed, Qamar Uddin; Umar, Abdulrashid; Muhammad, Bala Yauri; Dogarai, Bashar Bello S. (2009)
Background review: The WHO estimates that, currently, more than 246 million people worldwide have diabetes. The number is anticipated to increase to 380 million by the year of 2050. Natural products are excellent sources of lead compounds in the search for novel drugs for the treatment of various diseases. T. scandens Linn., (Mempelas Kesar)is an important medicinal plant widely used in folkloric medicine including Malaysia. The different parts of this plant have been found to act effectively in the treatment of gout, internal pains, sore throat, hepatitis and lowering hypertension traditionally. Objective: To explore the anti-diabetic potential of T. scandens in vivo. Methods: Glucose levels in rats with hypertension induced by alloxan (150 mg/kg b.w.) were determined after oral administration of both the aqueous and methanolic extracts of the leaves of T. scandens. Different doses of both extracts (250, 500, 1000 and 2000 mg/kg b.w.) were evaluated in normal, and alloxan induced diabetic rats. Results & Conclusion: The methanolic extract exhibited significant antihyperglycemic activity in diabetic rats at different doses stated above; however, the activity was found to be much stronger in the aqueous extract. In normal rats no hypoglycemic activity was observed when compared with the both diabetic and normal controlled groups. The fall of blood glucose was also found to comparable with the standard antidiabetic drug, glibenclamide (0.6 mg/kh b.w.). LD 50 of both the extracts was found to be above 5000 mg/kg body weight. Phytochemical screening vividly revealed the presence of terpenoids, alkaloids abd flavonoids which could be responsible for its antihyperglycemic effect. Our study reveals the fact the the leaves of T. scandens possess potential antidiabetic agents which significantly lower the blood glucose level in the diabetic rats and could be clinically screened further to find out its therapeutic potential towards the treatment of non-insulin dependent diabetes mellitus.